STUDY ON SENSITIZATION OF FULVIC ACID ON PHOTOREDUCTION OF Cr(VI) TO Cr(III) BY TiO2 PHOTOCATALYST - Uripto Trisno Santoso; Kamilia Mustikasaria; Sri Juari Santosa; Dwi Siswanta (Indonesian Journal of Chemistry, 2007)
Sensitization of fulvic acid (FA) on photoreduction of Cr(VI) to Cr(III) by TiO2 photocatalyst has been studied. Parameters influencing the sensitization, i.e., pH of medium, as well as FA concentrations, TiO2 concentrations and initial Cr(VI) concentrations were critically evaluated. Extraction of FA from peat soil sampled in Gambut, South Kalimantan, Indonesia, was performed using Amberlite XAD-7 resin. The FA extract then was purified by cation exchange method using Amberlite IRA-120 resin. The TiO2 produced by Merck was used as semiconducting photocatalyst and two 30-W UV lamps (Philips® model TUV) were used as photon source. The results showed that presence of FA on TiO2 suspensions could sensitize the photoreduction of Cr(VI), enhancing of the amount of reduced Cr(VI) more significantly than the sensitization by humic acid. The effectiveness of this sensitization increased with increasing initial concentrations of FA, TiO2, or Cr(VI) until certain concentration, but no further improvement can be observed in excess FA, TiO2, or Cr(VI) concentrations. On the contrary, the effectiveness of this sensitization decreased with increasing of the medium pH.